PERAN PENYULUH PERTANIAN DALAM PENINGKATAN KAPASITAS PETANI KOPI ARABIKA DI KOTA SUNGAI PENUHI - Hamidi Hamidi; Gunarif Taib; Asmawi Asmawi (Agros Journal of Agriculture Science, 2023)
Increasing the capacity of Arabica coffee farmers in Sungai Penuh is an effort to increase the capacity of farmers through an extension approach, both in group training and individual training by government agricultural extension workers to improve technical skills in Arabica coffee cultivation, managerial and building partnership networks. For this reason, research was carried out which seeks to understand the role of agricultural extension in increasing the capacity of arabica coffee farmers in Sungai Penuh. This research is a qualitative research and categorized as descriptive research. The results of this study are the role of agricultural extension workers in increasing the capacity of arabica coffee farmers, both technical cultivation, managerial and partnership networking by coffee farmers in Sungai Penuh is in the medium category. The capacity of Arabica coffee farmers in Sungai Penuh, consisting of cultivation techniques, management and partnership networks. The lowest capacity is managerial and partnership, while the highest is cultivation technical capacity.INTISARIPeningkatan kapasitas petani kopi arabika di kota sungai penuh merupakan upaya peningkatan kemampuan petani melalui pendekatan penyuluhan baik anjang sana kelompok maupun anjang sana perorangan oleh penyuluh pertanian pemerintah untuk meningkatkan kemampuan dalam hal teknis budidaya kopi arabika, manajerial dan membangun jejaring kemitraan. Untuk itu dilakukan penelitian yang berupaya untuk memahami peran penyuluhan pertanian dalam peningkatan Kapasitas  Petani Kopi Arabika di Kota Sungai Penuh. Penelitian ini merupakan penelitian kualitatif dan dikategorikan sebagai penelitian deskriptif. Hasil dari penelitian ini adalah peran penyuluh pertanian terhadap peningkatan kapasitas petani kopi arabika baik teknis budidaya, manajerial dan jejering kemitraan oleh petani kopi di Kota Sungai Penuh berada pada kategori sedang. Kapasitas petani kopi arabika di kota sungai penuh, terdiri dari teknis budidaya, manajerial dan jejaring kemitraan. Kapasitas paling rendah yaitu manajerial dan kemitraan, sedangkan yang paling tinggi adalah kapasitas teknis budidaya.